Comparison of 68Ga-DOTATOC-PET/CT and PET/MRI hybrid systems in patients with cranial meningioma: Initial results - Afshar-Oromieh, Ali; Wolf, Maya Barbara; Kratochwil, Clemens; Giesel, Frederik L.; Combs, Stephanie; Dimitrakopoulou-Strauss, Antonia; Schlemmer, Heinz-Peter; Haberkorn, Uwe (Neuro-Oncology, 2015)
Comparison of ⁶⁸Ga-DOTATOC-PET/CT and PET/MRI hybrid systems in patients with cranial meningioma: Initial results
Published online: 9 July 2014
Gesehen am 30.06.2017